The mineralogy and geochemistry of Neogene sediments from eastern Turkey, southeast of Arapgir (Malatya) - Bal Akkoca, Dicle; Baytasoglu, Zeynep (Tubitak Scientific & Technological Research Council Turkey, 2013)
The mineralogy and geochemistry of volcaniclastic sediments in the southeastern part of the Arapgir area (Malatya) were studied by optical microscopy, XRD, SEM, ICP-AES, and MS techniques. Samples were collected from the marine and lacustrine deposits of the Dibekli and Bogurludag sections that contained calcite, clay minerals, feldspar, quartz, dolomite, and opal. Clay minerals were mixed layer smectite-chlorite, illite, and palygorskite, with Ca-smectite being the dominant clay phase. Smectite was derived from the transformation of volcanic glass and volcanic rock fragments. The fact that Y, Sc, Co and Sigma REE concentrations and (La/Lu)N, La/Sc, Sc/Th, Co/Th, Th/U, and Zr/Hf ratios of tuffites of marine and lacustrine formations are quite similar suggests that these deposits had a common source. The marine sediments of the Alibonca Formation under the volcano sedimentary units are derived from Yamadag volcanic products and, therefore, volcanism might have commenced in the Lower Miocene.
Keywords: Yamadag Volcanics; marine and lacustrine sediments; clay mineralogy